Work-Family Conflict and Mental Health among Healthcare Workers: The Moderating Role of Work-Family Conflict Self-Efficacy - Balogun, Anthony G.; Adetunji, Adeola M.; Uye, Emmanuel E. (MultiTech Publisher, 2024)
Healthcare workers experience multifaceted mental health issues due to the nature of their work. Some studies have investigated predictors of mental health with varied results. Therefore, this study examined moderating roles of work-family conflict self-efficacy (WFCSC) on the relationship between work-family conflict and mental health among healthcare workers in Akure metropolis, Ondo State, Nigeria. The study adopted cross-sectional survey design while purposive sampling technique was used to select three state hospitals in Akure metropolis. Data were collected from 201 healthcare workers using validated scales and analyzed using zero-order correlation and three-step hierarchical multiple regression to test three hypotheses. All hypotheses were accepted at p < .05 level of significance. The result indicated that work-family conflict significantly predicted mental health among study participants. Also, the result revealed that WFCSE significantly predicted mental health among healthcare workers. Finally, the result showed that WFCSE significantly moderated the relationship between work-family conflict and mental health among healthcare workers). The study concluded that WFCSE is a strong predictor and moderator of mental health among study participants. Therefore, it is recommended that management should provide mental health support services to their workers to reduce the negative influence of work-family conflict self-efficacy on mental health outcomes.